Social Justice, Multicultural Counseling, and Practice Beyond a Conventional Approach - Jun, Heesoon (Springer International Publishing, 2018)
This second edition book provides an update to multicultural psychology and counseling research findings, and the DSM-5 in sociopolitical and cultural contexts. It links social psychology with current cognitive science research on implicit learning, ethnocentrism (attribution error, in-group favoritism, and asymmetric perception), automatic information processing, and inappropriate generalization. Chapters discuss the interwoven characteristics of multiple identities of individuals such as race, gender, class, disability, age, religion, region, and sexual orientation. In addition, the book offers concrete strategies to facilitate inner-dialogue and discussion of self-perception and interpersonal relationships. Featured topics in this book include: Intrapersonal communication and the biases that can be involved. The impact of a provider's personal values and beliefs on assessing and treating clients. The Social Categorization Theory of Race. The Social Categorization Theory of Gender. The Social Dominance Theory of Class. Identity Construction, Multiple Identities, and their intersectionality. Social Justice, Multicultural Counseling, and Practice, Second Edition will be of interest to researchers and professors in clinical psychology, counseling psychology, multicultural psychology, social psychology, cognitive neuroscience, social work, social justice, equity, and inclusion work as well as health care providers.